2015
DOI: 10.1016/j.ijmecsci.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Imperfection sensitivity of thin-walled I-section struts susceptible to cellular buckling

Abstract: A variational model that describes the nonlinear interaction between global and local buckling of an imperfect thin-walled I-section strut under pure compression is developed. An initial out-of-straightness of the entire strut and an initial local out-of-plane displacement in the flanges are introduced as a global and a local type of imperfection respectively. A system of differential and integral equilibrium equations is derived for the structural component from variational principles, an approach that was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…where z ∈ [0, L] and the imperfection is symmetric about z/L = η. Since previous work on sandwich panels [22], I-section struts [23], stiffened plates [24] and functionally graded carbon nanotube-reinforced composite beams [52] have demonstrated that the worst case occurs when the local imperfection is symmetric about midspan, the value of η is selected to be 1/2. The quantity A 0 controls the amplitude of the imperfection component.…”
Section: Imperfections Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…where z ∈ [0, L] and the imperfection is symmetric about z/L = η. Since previous work on sandwich panels [22], I-section struts [23], stiffened plates [24] and functionally graded carbon nanotube-reinforced composite beams [52] have demonstrated that the worst case occurs when the local imperfection is symmetric about midspan, the value of η is selected to be 1/2. The quantity A 0 controls the amplitude of the imperfection component.…”
Section: Imperfections Descriptionmentioning
confidence: 99%
“…Even though the possible individual buckling modes taken in isolation are stable or neutral in terms of their post-buckling behaviour, the triggering of various combinations of modes simultaneously can lead to a violent destabilization after the ultimate load is reached [13,14,15,16,17]. More importantly, such structural components tend to be highly sensitive to imperfections [18,19,20,21,22,23,24,25]; a tiny imperfection may lead to a significant erosion in the load-carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression is derived from a leading-order solution to a multiple scale perturbation analysis of a strut on a nonlinear softening foundation, which matches the least stable localized buckling mode shape closely [22]. The quantities α and β control the degree of localization and the periodic frequency of the imperfection shape respectively and are currently chosen to match the initial local buckling eigenmode found in earlier work [23].…”
Section: Modal Descriptionsmentioning
confidence: 99%
“…The interaction between individual modes can lead to a profound change in the post-buckling behaviour, even though these modes may be stable when triggered in isolation. In particular, such systems can exhibit a violent destabilization after the peak load is reached [9,10,11] and, in certain parametric ranges, have been demonstrated to be highly sensitive to initial geometric imperfections [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%